Association between Noise Exposure and Sensitivity and Psychological Distress - Seyed Hojat Mousavi Kordmiri; Mohamad Reza Monazzam; Milad Abbasi; Sepideh kamali; Seyedeh Azam Mousavi Kordmiri (Archives of Occupational Health, 2019)
Background: Noise pollution is considered as a major threat to human society that may affect life quality, efficiency, physical and mental health. Therefore, the present study was aimed to investigate the effects of noise exposure and noise sensitivity on psychological distress in an automobile parts manufacturer's employees. Methods: In this descriptive-analytical study, 325 employees of an automobile parts manufacturer who were exposed to different noise levels in seven groups were investigated. Daily personal noise exposure for each group was measured using calibrated sound level meter (SVANTEK-971) based on ISO-9612 standards. Then employees' mental disorder and noise sensitivity were determined using Kessler Psychological Distress Scale and Weinstein's Noise Sensitivity Scale (WNSS), respectively, and data was analyzed using SPSS v. 23. Results: Mean psychological distress was significantly different between noise sensitivity and noise exposure groups (P-value <0.05). Based on the results of multiple regression analysis among four variables including age, work experience, noise exposure and noise sensitivity, noise exposure and noise sensitivity had significant effect on psychological distress and could explain 0.36 and 0.25 of variance of response variable, respectively. Age and work experience at the level of 5% error had no significant effect on psychological distress status. Conclusion: It can be argued that the worsening of psychological distress in these employees is often due to noise exposure and noise sensitivity. As an individual variable, noise exposure has the greatest effect on increase of psychological distress compared to noise sensitivity level and demographic characteristics studied.